Building a structural model: Parameterization and structurality - Michel Mouchart; Renzo Orsi (Econometrics, 2016)
A specific concept of structural model is used as a background for discussing the structurality of its parameterization. Conditions for a structural model to be also causal are examined. Difficulties and pitfalls arising from the parameterization are analyzed. In particular, pitfalls when considering alternative parameterizations of a same model are shown to have lead to ungrounded conclusions in the literature. Discussions of observationally equivalent models related to different economic mechanisms are used to make clear the connection between an economically meaningful parameterization and an economically meaningful decomposition of a complex model. The design of economic policy is used for drawing some practical implications of the proposed analysis.
Keywords: C10; C18; C50; C51; C54; 330; structural model; recursive decomposition; exogeneity; causality; model identification; observationally equivalent models; structural invariance; misleading constraints; structurality